Creating tools for academic advising and evaluating its efficiency - Nguyen, Duy Mộng Hà (Journal of Technical Education Science, 2015)
Since the universities and colleges in the whole country adopted credit-based system, most of them have mainly focused on arranging study hours for the courses/modules as well as developing structures and contents for the study programs, mechanism for credit registration and class organization while academic advising which is a crucial part of credit-based system has not been considered with due attention. Many universities have no experience in running the academic advising system effectively and there have been an increasing number of disputes about the roles and competencies of academic advisers. One of the solutions given is the appropriate assignment together with the improvement of academic advisers’ competencies. However, there is a lack of experts in this field. Therefore, the paper recommends some ways of developing academic advising systematically: from establishing appropriate mechanism, policies, assignments and improving advising competencies to monitoring and reviewing this activity periodically for continuous improvement as well as sharing best practices. It is therefore necessary to create a set of tools for implementing and evaluating academic advising